UPAYA MENINGKATKAN HASIL BELAJAR IPS DENGAN MENERAPKAN METODE TIME TOKEN ARENDS PADA SISWA KELAS VII SMP NEGERI 1 GAUNG - Susi Kurniati (JURNAL RANDAI, 2020)
This study aims to improve the social studies learning outcomes of Grade VII students of SMP Negeri 1 Gaung by applying the Time Token Arends method. This research is a Classroom Action Research conducted in 3 (three) cycles with stages of planning, implementation and observation, and reflection. Where each cycle consists of 1 (one) meeting. The conclusion of this study is that the Time Token Arends method has a positive impact in improving student learning outcomes which is characterized by an increase in student learning completeness in each cycle, namely cycle I (27.59%), cycle II (51.72%) and cycle III (89.66%).